Relationship between amputation and risk factors in individuals with diabetes mellitus: A study with Brazilian patients - Mantovani, Alessandra M. [UNESP]; Fregonesi, Cristina E. P. T. [UNESP]; Palma, Mariana R. [UNESP]; Ribeiro, Fernanda E. [UNESP]; Fernandes, Romulo A. [UNESP]; Christofaro, Diego G. D. [UNESP] (Elsevier B.V., 2017)
Individuals with diabetes develop lower extremity amputation for several reasons. Investigations into pathways to the development of complications are important both for treatment and prevention. Aim: To evaluate the relationship between amputation and risk factors in people with diabetes mellitus. Materials and method: All participants included in this study (n = 165) were recruited from the Diabetic Foot Program, developed in a Brazilian University, over seven years (2007-2014) and all information for this study was extracted from their clinical records. Results: The prevalence of amputation in patients with diabetes with four risk factors was up to 20% higher when compared to those with only one risk factor. The main predictive risk factors for amputation in this population were the presence of an ulcer and smoking. Conclusion: The risk factors for amputation can be predicted for people with diabetes mellitus and, in the present study, the main factors were the presence of an ulcer and the smoking habit. (C) 2016 Diabetes India. Published by Elsevier Ltd. All rights reserved.
Keywords: Diabetes mellitus; Risk factor; Diabetic neuropathy; Amputation; Diabetic foot